2006
DOI: 10.1161/01.str.0000245081.52877.f2
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Surgery Is Associated With Reduced Occurrence of Stroke and Other Morbidity as Compared With Traditional Coronary Artery Bypass Grafting

Abstract: Background and Purpose-There is growing enthusiasm for coronary artery bypass grafting (CABG) without cardiopulmonary bypass (CPB). Although deleterious effects of CPB are known, it remains to be proven that avoiding CPB will result in reduction in morbidity. We sought to determine whether off-pump surgery is associated with reduced occurrence of adverse outcomes as compared with CABG with CPB. Methods-Studies were identified by searching the MEDLINE, EMBASE and the Cochrane Register 1980. We also searched the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 77 publications
5
82
0
3
Order By: Relevance
“…Complete off-pump procedures in the hands of trained surgical teams seem to be associated with a reduced risk of stroke, AF, respiratory and wound infections, less transfusion, and shorter hospital length of stay [201]. Highly experienced teams obtain similar 1-year outcomes, graft patency, and quality of life with offpump vs. on-pump approaches.…”
Section: Early Post-operative Riskmentioning
confidence: 95%
“…Complete off-pump procedures in the hands of trained surgical teams seem to be associated with a reduced risk of stroke, AF, respiratory and wound infections, less transfusion, and shorter hospital length of stay [201]. Highly experienced teams obtain similar 1-year outcomes, graft patency, and quality of life with offpump vs. on-pump approaches.…”
Section: Early Post-operative Riskmentioning
confidence: 95%
“…It has been reported that off-pump coronary bypass surgery can reduce SSI. Sedrakyan et al [22] showed in a meta-analyzes that wound infections could be reduced by 48% at the same risk as compared with on-pump surgery (RR, 0.52; 95% CI, 0.37 to 0.74). Risk difference analyzes showed 40 SSI prevented per 1000 coronary bypass surgeries with an off-pump approach.…”
Section: Incidence Of Ssi Discussionmentioning
confidence: 99%
“…Two additional prospective RCTs, focusing on elderly and high-risk patients, had failed to demonstrate a difference in 30-day or 1-year outcomes when on-or off-pump CABG was performed by experienced teams [50,51]. Interestingly, based on some of the same data available to the American group [47,52], the Europeans were more convinced of the potential value of off-pump surgery in high-risk patients, especially with regard to stroke, and recommended that off-pump CABG be 'considered' for subgroups of high-risk patients in high-volume off-pump centres as a COR IIa based on LOE B. Like their American colleagues, the European group was even more definitive regarding minimization of aortic manipulation and 'recommended' off-pump CABG and/or no touch on-pump techniques for patients with significant atherosclerotic aortic disease as a COR I with LOE B.…”
Section: On-versus Off-pumpmentioning
confidence: 99%